2017
DOI: 10.1016/j.conbuildmat.2016.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Combined Non-Destructive Testing (NDT) method for the evaluation of the mechanical characteristics of Ultra High Performance Fibre Reinforced Concrete (UHPFRC)

Abstract: Ultra-High Performance Fibre Reinforced Concrete is a material which is becoming increasingly popular in structural applications, mainly due to its superior mechanical characteristics. The mechanical properties of this material are of high importance and the development of non-destructive techniques is vital for the evaluation of the mechanical characteristics of existing structures. In the current study, Ultra-High Performance Fibre Reinforced Concrete with different amounts of steel fibres has been examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 24 publications
(31 reference statements)
2
22
0
6
Order By: Relevance
“…These observations imply that the addition of fibers does not significantly influence Young's modulus of concrete irrespective of the type and dosage of fibers. This is similar to those reported by ACI and some researchers, such as Noushini et al and Tsioulou et al . Nevertheless, when the volume fraction of PVA fiber increases, a decreased modulus of elastic is anticipated for PFR‐UHSC due to the lower modulus of fibers themselves …”
Section: Results and Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…These observations imply that the addition of fibers does not significantly influence Young's modulus of concrete irrespective of the type and dosage of fibers. This is similar to those reported by ACI and some researchers, such as Noushini et al and Tsioulou et al . Nevertheless, when the volume fraction of PVA fiber increases, a decreased modulus of elastic is anticipated for PFR‐UHSC due to the lower modulus of fibers themselves …”
Section: Results and Analysessupporting
confidence: 91%
“…Compared with the compressive strengths obtained from cubic and prism plain UHSC (namely, V f = 0) specimens, the counterparts of SFR‐UHSC specimens with V f = 1.0% are increased by 3.49 and 8.44%, respectively. Moreover, the enhancement of compressive strength caused by steel fibers increases with an increasing fiber content in our previous work and experiment of Tsioulou et al When it comes to PFR‐UHSC, it can be seen from Table and Figure that its cubic compressive strengths were decreased by 5.24, 6.64, and 13.28%, respectively, for the three dosages of fibers while the corresponding reduction for prism compressive strengths were 3.22, 6.17, and 9.26%. This phenomenon may be explained by considering the fact that Young's modulus of PVA fiber is lower than that of UHSC matrix, resulting in a weaker constraint when subjected to compression.…”
Section: Results and Analysessupporting
confidence: 54%
“…Results showed that, from normally vibrated concrete to Ultra-High Strength concrete and the water powder ratio, the water-binder ratio, and the admixtures relatively has influence on the rebound index number and compressive strengths. Ourania Tsioulou et al [11] studies shows, the evaluation of tensile strength and the Compressive strength using UPV and Rebound Hammer measurements. Author uses the combination of methods in his analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of researchers as in [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20] and [21] exercised DT and NDT methods and proposed numerous relationships between the two.…”
Section: Introductionmentioning
confidence: 99%